2013
DOI: 10.1128/aem.00635-13
|View full text |Cite
|
Sign up to set email alerts
|

Regulon Studies and In Planta Role of the BraI/R Quorum-Sensing System in the Plant-Beneficial Burkholderia Cluster

Abstract: fThe genus Burkholderia is composed of functionally diverse species, and it can be divided into several clusters. One of these, designated the plant-beneficial-environmental (PBE) Burkholderia cluster, is formed by nonpathogenic species, which in most cases have been found to be associated with plants. It was previously established that members of the PBE group share an N-acyl-homoserine lactone (AHL) quorum-sensing (QS) system, designated BraI/R, that produces and responds to 3-oxo-C 14 -HSL (OC14-HSL). Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…The BraI/R QS system was found to be upregulated in the presence of rice plant macerate in the RNAseq experiment. Transcriptome studies have been performed to identify the BraI/R regulon in other closely related species of plant-beneficial Burkholderia spp., highlighting the fact that it is species-specific and no core regulon is present (Coutinho et al 2013a). Currently, the BraI/R regulon of B. kururiensis M130 is unknown and it is likely that it regulates loci that play important roles in endophytism.…”
Section: Discussionmentioning
confidence: 99%
“…The BraI/R QS system was found to be upregulated in the presence of rice plant macerate in the RNAseq experiment. Transcriptome studies have been performed to identify the BraI/R regulon in other closely related species of plant-beneficial Burkholderia spp., highlighting the fact that it is species-specific and no core regulon is present (Coutinho et al 2013a). Currently, the BraI/R regulon of B. kururiensis M130 is unknown and it is likely that it regulates loci that play important roles in endophytism.…”
Section: Discussionmentioning
confidence: 99%
“…In the same way, endophytic colonization, germination, and plant-growth promotion of maize by Burkholderia phytofi rmans PsJN is not impacted in a strain defi cient in AHL production (Coutinho et al 2013 ). On the contrary, the BraIR QS system of Burkholderia kuriensis has been shown to be important for endophytic colonization of rice (SuarezMoreno et al 2010 ).…”
Section: Screening Of Qs Regulated Functions By Phenotypic Assaysmentioning
confidence: 96%
“…These global omics approaches revealed that QS can affect several percent of the protein or gene content in bacteria, as observed for B. phymatum or Rhizobium leguminosarum (Coutinho et al 2013 ;Cantero et al 2006 ).…”
Section: Omics Approaches To Identify Qs-regulated Genesmentioning
confidence: 97%
See 1 more Smart Citation
“…AHL molecule secreted from B. Phytofirmans PsJN affects root colonization and plant growth by auxin signaling in plants [12]. Coutinho and coworkers in 2013 identified 3-oxo-dodecanoyl homoserine lactone is expressed in highest amount among the different 3-oxo-AHLs produced by the BraI/R system of B. phytofirmans PsJN [13]. To identify the binding site of ARR10 of Arabidopsis thaliana with most expressed AHL, in our present work we dock ligand 3-oxo-dodecanoyl homoserine lactone with that protein.…”
Section: Introductionmentioning
confidence: 99%